2015
DOI: 10.1002/mnfr.201500184
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index mediates inflammatory response to acute dietary challenges

Abstract: Our results indicate that BMI is strongly linked to the transcriptomic and metabolic response to acute challenges. The emerging biological processes are mainly inflammation-related pathways, highlighting an interconnection between obesity, inflammation/adhesion, and response to nutritional challenge. The comparison between lipid and glucose challenges shows how these trigger a substantially different molecular response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Furthermore, fatty acids are known to be inflammatory modulators and immune responses can be activated by saturated fatty acids . The MECHE cohort study group previously highlighted inflammatory and metabolic biomarkers and altered genes expression in an age and BMI‐dependent manner . However to date there was little appreciation of the gender dependency in terms of metabolic responses to metabolic challenges, which is potentially important since gender greatly influence dietary intake and nutrient responses .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, fatty acids are known to be inflammatory modulators and immune responses can be activated by saturated fatty acids . The MECHE cohort study group previously highlighted inflammatory and metabolic biomarkers and altered genes expression in an age and BMI‐dependent manner . However to date there was little appreciation of the gender dependency in terms of metabolic responses to metabolic challenges, which is potentially important since gender greatly influence dietary intake and nutrient responses .…”
Section: Discussionmentioning
confidence: 99%
“…The postprandial response to an oral lipid tolerance test (OLTT) is a better metabolic challenge to emulate nutrient overload, in comparison to an oral glucose tolerance test (OGTT) . To study the impact of nutritional challenge on metabolism and inflammation, peripheral blood mononuclear cells (PBMC) transcriptome profiling has proved meaningful . Previously our group identified differential transcriptomic responses in inflammation‐related pathways following acute glucose or lipid challenges in the PBMC transcriptome of healthy adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Bouwens et al., Matone et al., and Esser et al. were previously published and data is publicly available (GSE13466, GSE56609, and GSE53232 at Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/geo)). These studies used single‐channel Affymetrix microarrays to perform gene expression measurements, whereas the fourth study (Fat_challenge_tests) used llumina HumanHt12‐v4 Expression Beadchips.…”
Section: Methodsmentioning
confidence: 99%
“…found that a high‐SFA challenge induced expression of liver X receptor signaling genes, whereas a high‐PUFA challenge caused a downregulation of these genes. Matone et al . studied the effects of a high‐MUFA challenge and observed increased expression of inflammatory genes in several pathways, including Toll‐like receptors, interleukins, tumor necrosis factor, and nuclear factor κB‐related genes.…”
Section: Introductionmentioning
confidence: 99%